2005
DOI: 10.1021/ma047846y
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Polystyrene Molecular Weight and Modification to the Repeat Unit Structure on the Glass Transition−Nanoconfinement Effect and the Cooperativity Length Scale

Abstract: The effect of nanoconfinement on the glass transition temperature (T g) of supported polystyrene (PS) films is investigated over a broad molecular weight (MW) range of 5000−3 000 000 g/mol. Polystyrene MW is shown to have no significant impact on the film thickness dependence of T g − T g,bulk. In contrast, a small modification to the repeat unit structure of PS has a dramatic impact on the T g-nanoconfinement effect. The strength of the thickness dependence of T g is greater for poly(4-methylstyrene) (P4MS) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
386
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(420 citation statements)
references
References 83 publications
28
386
6
Order By: Relevance
“…1), which can be explained by assuming that for d≥35 nm, the error in the determination of T g is larger than the effective ∆T g . These last two results are in agreement with previous investigation of PS that showed no variation in T g (or ∆T g < 2 K) above 40 nm or any impact of M w on T g (d) 42 .…”
Section: Figure 3 | Distribution Of Relaxation Times and Interfacial supporting
confidence: 93%
“…1), which can be explained by assuming that for d≥35 nm, the error in the determination of T g is larger than the effective ∆T g . These last two results are in agreement with previous investigation of PS that showed no variation in T g (or ∆T g < 2 K) above 40 nm or any impact of M w on T g (d) 42 .…”
Section: Figure 3 | Distribution Of Relaxation Times and Interfacial supporting
confidence: 93%
“…Such Broadening, no broadening and narrowing of glass transition C Yang and I Takahashi increased mobility near the substrate would come from the enhanced mobility in the free-surface region, which increases the degree of homogeneity by decreasing the difference of mobility among the three layers. Measurements of a 14-nm-thick fluorescently labeled PS layer embedded in a thick PS layer 8 showed that the enhanced mobility inherent in the free-surface region can propagate into the interior of the film as deep as 20-30 nm, which is much longer than the length scale of a single cooperatively rearranging region reported for bulk PS (B3.5 nm); 30 once the mobility of segments in the topmost surface layer is enhanced, it would yield a series of perturbations toward the adjacent interior layer, leading a dynamics perturbation into the interfacial layer. 8,31,32 It is thus quite likely that in ultrathin films under such ultraslow temperature variation, the enhanced mobility in the surface region can slowly propagate into the interfacial layer via the interior layer, until it finally modifies local dynamics of the interfacial layer.…”
Section: Discussionmentioning
confidence: 98%
“…This relatively small depression in T g (20 • C) is smaller than that has been observed in polystyrene, where a T g reduction up to 40…”
Section: Resultsmentioning
confidence: 58%
“…Ellison et al [20] also found that modification of the PS monomer unit can substantially change the T g deviation behavior, and concluded that chain stiffness is responsible for increased onset thickness of the depressed-T g surface layer via its influence on the cooperative segmental size of the polymers. We conclude therefore that PCDTBT has a higher chain stiffness than PS, resulting in a comparatively larger cooperative segmental size and a higher onset thickness for T g deviation.…”
Section: Resultsmentioning
confidence: 99%